(untitled) (Altifani : Jurnal Pengabdian Masyarakat Ushuluddin, Adab, dan Dakwah, 2024)
Stunting is still a problem, especially in Kerinci Regency because so far it has the highest prevalence of stunting among 11 districts/cities. This writing aims to formulate policies in an effort to accelerate the reduction of stunting in Kerinci Regency. Mixed method approach by conducting Focus Group Discussions and in-depth interviews with 25 stake holders/members of TPPS as well as quantitatively analyzing PK-21 data and other supporting data such as E-PPGBM, situation analysis master data, 2018 Riskesdas data, Regency Profiles from BPS. Some of the causes of stunting in toddlers are parenting and wrong eating patterns (lack of nutritional intake), welfare or socioeconomic level, marriage or pregnancy too young, environmental health, malnourished pregnant women (KEK), micronutrient deficiencies (anemia) and lack of implementation of PHBS . Local Government regulations and commitments with the Regent’s Regulations for stunting prevention and other supporting regulations already exist. Several obstacles in accelerating the reduction of stunting, namely the Stunting Care Youth Program has not yet been implemented, the synergy of convergence actions and Pentahelix has not been optimal, weak coordination of planning, budgeting, implementation, monitoring and evaluation, limited capacity and quality of organizers, lack of budget, differences in public perceptions of stunting, lack of the number and capacity of human resources, data availability and program planning have not been integrated. It is necessary to strengthen commitment, synergy and synchronization of integrated multi-stakeholder stunting prevention programs and comprehensive interventions as well as increased communication, information, education for changing people’s healthy behavior.